Heritability Analysis of Cytokines as Intermediate Phenotypes of Tuberculosis - Stein, Catherine M.; Guwatudde, David; Nakakeeto, Margaret; Peters, Pierre; Elston, Robert C.; Tiwari, Hemant K.; Mugerwa, Roy; Whalen, Christopher C. (The Journal of infectious diseases, 2003)
Numerous studies have provided support for genetic susceptibility to tuberculosis (TB); however, heterogeneity in disease expression has hampered previous genetic studies. The purpose of this work was to investigate possible intermediate phenotypes for TB. A set of cytokine profiles, including antigen-stimulated whole-blood assays for interferon (IFN)–g, tumor necrosis factor (TNF)–a, transforming growth factor (TGF)–b, and the ratio of IFN to TNF, were analyzed in 177 pedigrees from a community in Uganda with a high prevalence of TB. The heritability of these variables was estimated after adjustment for covariates, and TNF-a, in particular, had an estimated heritability of 68%. A principal component analysis of IFN-g, TNF-a, and TGF-b reflected the immunologic model of TB. In this analysis, the first component explained 138% of the variation in the data. This analysis illustrates the value of such intermediate phenotypes in mapping susceptibility loci for TB and demonstrates that this area deserves further research.
Keywords: Heritability Analysis; Cytokines; Phenotypes; Tuberculosis